A Correlation Study Between Listening And Pronunciation Skills of Efl Learners: English - Snae, Alfred; Beeh, Norci; Nenotek, Seprianus A (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
This article aimed in finding out the correlation between students’ scores in listening and pronunciation tests, the degree of the correlation, and the contribution of listening towards pronunciation and vice versa. It is a correlational study to find out the correlation between listening and pronunciation and chose 25 students of first semester as the representative subjects in conducting this research. The result shows that there is a correlation between listening and pronunciation skills, which are shown by the index of correlation, that are 0, 008 and 0, 031 as the results of both tests given. These results are classified as a slight correlation. So, there is no significant contribution for both variable.